Experimental and Theoretical Investigations in ECDM Process – An Overview. (2016) - Paul, Lijo; Hiremath, Somashekhar S.
Abstract: The need for micro- machining of advanced engineering material started with increasing demand in aerospace, nuclear and medical industries. Hybrid machining processes are introduced through the combination of the many non-conventional machining processes thereby taking the advantage of more than one process. Electro Chemical Discharge Machining (ECDM) is a novel hybrid machining process used for machining conducting and non-conducting engineering materials combining the features of EDM and ECM processes. The present paper focuses on the theoretical study, design and development of experimental setup, experimental investigation and control strategies in ECDM process, carried out so far by many researchers.